Phylogenetic and transcripts profiling of glucose sensing related genes in Candida glabrata - Ng, Tzu Shan; Mohd Desa, Mohd Nasir; Sandai, Doblin; Chong, Pei Pei; Than , Leslie Thian Lung (Ahvaz Jundishapur University of Medical Sciences, 2015)
Background: The sensing mechanism of glucose in Saccharomyces cerevisiae is well studied. However, such information is scarcely found in other yeast species such as Candida glabrata. Objectives: This study aimed to identify the glucose sensing pathway related genes of C. glabrata and to analyze the regulation pattern of these genes in response to different surrounding glucose concentrations through the quantitative real time polymerase chain reaction (qRT-PCR). Materials and Methods: Phylogenetic analysis was carried out on predicted amino acid sequences of C. glabrata and S. cerevisiae to compare their degree of similarity. In addition, the growth of C. glabrata in response to different amounts of glucose (0%, 0.01%, 0.1%, 1% and 2%) was evaluated via the spot dilution assay on prepared agar medium. Besides, the SNF3 and RGT2, which act as putative glucose sensors, and the RGT1 and MIG1, which act as putative transcriptional regulators and selected downstream hexose transporters (HXTs), were analysed through qRT-PCR analysis for the gene expression level under different glucose concentrations. Results: Comparative analysis of predicted amino acids in the phylogenetic tree showed high similarity between C. glabrata and S cerevisiae. Besides, C. glabrata demonstrated the capability to grow in glucose levels as low as 0.01% in the spot dilution assay. In qRT-PCR analysis, differential expressions were observed in selected genes when C. glabrata was subjected to different glucose concentrations.